A Detection and Prevention of Ddos Attacks - Gupta, Anjulee; Patel, Brajesh (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, cloud computing is very important because of its benefits. But it is also prone to attacks due to vulnerabilities of the websites. DDoS is distributed denial of service where Trojan infected computers are used to target a system to cause traffic jams and genuine users can not able get the service of websites. DDOS affects internet services like e- commerce, e-banking, education, medicine, reservations, agriculture etc. In this way both the end systems are controlled by hackers. There are three categories – volume-based attacks, protocol attacks and application attacks. The companies they are implementing no. of solutions to defend the attacks and continuously updating their techniques but attackers also updating their techniques and methods of attacks. So, in this paper the system is made to collect data online and with the help of association rule mining ddos attack are detected and prevented. Here techniques are used to properly detect attackers and genuine users so that cloud services can be given the users.